SELF TRANSCENDENCE: THE IDEALITY DIMENSIONS OF AL-ISLAM AND KEMUHAMMADIYAHAN LEARNING IMPACT IN MUHAMMADIYAH SCHOOL - Rofi, Sofyan; Setiawan, Bahar Agus; Hanafi, Hanafi (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
The terms al-Islam and Kemuhammadiyahan used by Muhammadiyah schools for learning Islamic religious education are in line with the educational objectives contained in the national education law. Developing the potential of students to have religious spiritual strength is a concrete form of achievement to be realized through the implementation of education. This context has an equivalent to the hierarchy of self-transcendence which is the final level of Maslow's theory of needs. This qualitative-based research with a case study uses a content analysis model on student answers in the form of a description with 1 single question. Respondents used as many as 379 students in Muhammadiyah schools at the junior high school level. The results showed that 53 students' answers lead to a desire to achieve the hierarchical dimension of self-transcendence which is reflected in changes in behavior. Based on the results of the study, it can be concluded that in the perspective of students learning al-Islam to achieve the ideal dimension, namely self-transcendence.